Concurrent evolution of resistance and tolerance to potato virus Y in Capsicum annuum revealed by genome‐wide association. (2nd November 2021) - Tamisier, Lucie; Szadkowski, Marion; Girardot, Grégory; Djian‐Caporalino, Caroline; Palloix, Alain; Hirsch, Judith; Moury, Benoit
Abstract: We performed a genome‐wide association study of pepper ( Capsicum annuum ) tolerance to potato virus Y (PVY). For 254 pepper accessions, we estimated the tolerance to PVY as the coefficient of regression of the fresh weight (or height) of PVY‐infected and mock‐inoculated plants against within‐plant virus load. Small (strongly negative) coefficients of regression indicate low tolerance because plant biomass or growth decreases sharply as virus load increases. The tolerance level varied largely, with some pepper accessions showing no symptoms or fairly mild mosaics, whereas about half (48%) of the accessions showed necrotic symptoms. We found two adjacent single‐nucleotide polymorphisms (SNPs) at one extremity of chromosome 9 that were significantly associated with tolerance to PVY. Similarly, in three biparental pepper progenies, we showed that the induction of necrosis on PVY systemic infection segregated as a monogenic trait determined by a locus on chromosome 9. Our results also demonstrate the existence of a negative correlation between resistance and tolerance among the cultivated pepper accessions at both the phenotypic and genetic levels. By comparing the distributions of the tolerance‐associated SNP alleles and previously identified PVY resistance‐associated SNP alleles, we showed that cultivated pepper accessions possess favourable alleles for both resistance and tolerance less frequently than expected under random associations, while the minority of wild pepper accessions frequently combined resistance and tolerance alleles. This divergent evolution of PVY resistance and tolerance could be related to pepper domestication or farmer's selection. Abstract : Among a core‐collection of pepper accessions, phenotypic and genetic negative correlations were found between resistance and tolerance to PVY for the cultivated pepper accessions, but not for the wild pepper accessions.